Butyric and docosahexaenoic acids production from hemicellulose - Zhang, Ling (Kansas State University, 2012)
Many of the current industrial fermentation processes cannot use pentose as the carbon source. However, complete substrate utilization of sugars in lignocellulose is one of the prerequisites to render economic development of biofuels or bioproducts from biomass. In this study we proposed a new process for DHA production from renewable carbon sources by first using anaerobic bacteria, Clostridium tyrobutyricum to convert pentose into organic acids with butyric acid as the main product, and then using the organic acids to feed microalgae, Crypthecodinium cohnii to produce DHA. The effect of glucose and xylose on the yield of butyric acid produced by C. tyrobutyricum was investigated, separately. Cell growth of C. tyrobutyricum increased with increasing initial glucose or xylose concentration, but was not affected significantly when the concentration was above 55g/l for glucose or 35g/l for xylose. Butyric acid yield increased as the initial sugar concentration increased in both xylose and glucose, but the conversion rate from xylose or glucose to butyric acid decreased as the sugar concentration increased. The xylose to glucose ratio in their mixture did not significantly affect cell growth or butyric acid yield. The effect of arabinose on the yield of butyric acid produced by C. tyrobutyricum was also studied. As for butyric acid production, compared with glucose or xylose, the arabinose was in a low efficiency, with butyric acid output of 2.25g/l in 10g/l arabinose and a long lag period of about 3-4 d. However, a low concentration of arabinose could be used as a nutritional supplement to improve the fermentability of a mixture of xylose and glucose. The conversion rate of sugar to butyric acid increased as the supplement arabinose increased. In order to obtain low cost xylose, corncobs were hydrolyzed and this xylose-rich product was used to culture C. tyrobutyricum. The results showed that at end of the 9 d fermentation, the concentration of butyric acid from corncob hydrolysate reached 10.56 g/l, and the mimic medium reached 11.3 g/l. This suggests that corncob hydrolysate can be used as a carbon source for butyric acid production by C. tyrobutyricum, although some inhibitory effects were found on cell growth with corncob hydrolysate. The effect of butyric acid, lactic acid and acetic acid on the yield of DHA produced by C. cohnii was also investigated, separately. The DHA yield was highly related to both biomass and DHA content in the cell, whereas lower growth rate could bring higher DHA content. The best concentration for DHA yield seemed to be 1.2g/l in three single organic acid media. In two organic acids mixture media, acetic acid tended to be beneficial for biomass accumulation, regardless whether butyric acid or lactic acid was mixed with acetic acid, the OD could reach 1.3 or above. When butyric acid was mixed with lactic acid, the highest DHA yield was achieved, due to increased DHA content from mutual influence between butyric acid and lactic acid.
Keywords: Butyric acid; DHA; Clostridium tyrobutyricum; C. cohnii; Engineering, Agricultural (0539)